De-mythologizing and re-branding of kava as the new 'world drug' of choice. (September 2019) - Aporosa, S Apo
What seemed impossible 50 years ago is today becoming a reality as 'soft drugs' such as cannabis are being decriminalized and accepted for their calming effects as well as their legitimate medicinal properties. Several countries have now made the possession of cannabis legal, with others considering this, while the coffee shops in the Netherlands have been supplying cannabis in different forms for many years. It is now the turn of kava to be re-evaluated, to see whether there are properties in this plant that might be readily substituted for more conventional and harmful drugs, for instance tobacco and alcohol. However, as highlighted by Norton and Ruze (1994), kava like cannabis, has an enduring reputation that still makes it difficult for many to accept. Kava has been mythologized as an illicit alcohol, highly addictive, and causing physical harm. When examining the history of kava use in traditional contexts and considering the evidence now available, it is possible to demythologize this characterization. Looking at the potential benefits, it is time to re-brand kava, not only on the grounds as a relaxant, but in possessing life enhancing medicinal properties and as an alternative to alcohol, understanding that will be beneficial to policy makers, doctors and pharmacists.